The clinical characteristics, putative drugs, and optimal management of 62 patients with stevens-johnson syndrome and/or toxic epidermal necrolysis: A retrospective observational study - Sujaya Manvi; Vikram K Mahajan; Karaninder S Mehta; Pushpinder S Chauhan; Sanket Vashist; Ravinder Singh; Prabal Kumar (Wolters Kluwer Medknow Publications, 2022)
Background: Case reviews of severe cutaneous adverse drug reactions (ADRs) such as SJS/TEN provide useful insights for clinical characteristics, putative drugs, and management protocols. Patients and Methods: Medical charts of 62 (m:f- 20:42) patients with SJS/TEN hospitalized between 2010 and 2019 were analyzed retrospectively for clinical attributes, putative drugs and their indications, extracutaneous complications, and therapeutic outcome. The diagnosis was clinical based on established criteria. WHO-UMC scale for reporting ADR and ALDEN algorithm score were used for causality assessment. Therapies were customized based on in-house resources and affordability. Results: Cases included were SJS (41.9%), SJS/TEN overlap (33.9%), and TEN (24.2%) aged 4-85 years. Complications included transaminitis (69.4%), lymphadenopathy (15.5%), septicemia (11.3%), and wound infections (4.8%). Aromatic anticonvulsants (37.1%), disease-modifying antirheumatic drugs (25.8%), antiretroviral drugs (12.9%), non-steroidal anti-inflammatory drugs (8.1%), antimicrobials (4.8%), and trihexyphenidyl (3.2%) were major putative drugs. The mean latent period was 16.6 days. The observed 8% mortality was because of primary comorbidities or multiorgan failure. Addition of fresh blood transfusion (BT, n = 11) or IVIg (n = 7) to systemic corticosteroids showed early relief in skin tenderness, improvement in general condition, and re-epithelialization. Only 16% of patients developed sequelae. Conclusion: Aromatic anticonvulsants, allopurinol, nevirapine, cotrimoxazole, paracetamol, and diclofenac remain the most implicated drugs. Sulfasalazine, leflunomide, ethambutol, and trihexyphenidyl were uncommon additions. A short course of high-dose dexamethasone in the early stage was useful. Addition of BT or IVIg provided rapid relief. Preexisting HIV disease, kidney disease, and sepsis remain important for in-hospital deaths. Retrospective study design and small number of cases remain major limitations.